2001
DOI: 10.1071/pp01061
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant system response of different wheat cultivars under drought: field and in vitro studies

Abstract: The participation of the antioxidant system in the drought tolerance of wheat cultivars (Triticum aestivum L.) was studied under field and in vitro conditions. Under field conditions, drought tolerance was evaluated by the capacity to maintain the grain yield under drought, which was higher in cvv. Elite and La Paz than in the sensitive cvv. Oasis and Cruz Alta. Tolerant cultivars showed lower relative water content (RWC) and lower above-ground vegetative biomass than sensitive cultivars. Field assays did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 0 publications
4
47
0
3
Order By: Relevance
“…GSH content increases with the accumulation of frost hardiness of Picea abies (Esterbauer and Grill 1978). An increase of GSH was observed after osmotic stress in wheat (Lascano et al 2001), suggesting that GSH aids in controlling the damage associated with osmotic injury. Wang and Deng (2004) found that GSH added during cryopreservation significantly increased regrowth of Citrus shoot tips.…”
Section: Introductionmentioning
confidence: 88%
“…GSH content increases with the accumulation of frost hardiness of Picea abies (Esterbauer and Grill 1978). An increase of GSH was observed after osmotic stress in wheat (Lascano et al 2001), suggesting that GSH aids in controlling the damage associated with osmotic injury. Wang and Deng (2004) found that GSH added during cryopreservation significantly increased regrowth of Citrus shoot tips.…”
Section: Introductionmentioning
confidence: 88%
“…For example, WD may have a protective role against heat stress but may exacerbate photoinhibition (Chaves et al 2002). Comparative field and in vitro studies on different wheat varieties established no clear correlation of water stress tolerance with some components of the antioxidant system activity under field conditions, but the existence of such a link was found under osmotic stress in vitro (Lascano et al 2001). Moreover, source-sink relations are a predominant factor at the reproductive stage on plant growth.…”
Section: Introductionmentioning
confidence: 97%
“…At a whole plant level crops have developed different strategies to counteract the negative effects of water limitation: increased water use efficiency, drought escape by shortening life cycle, dehydration avoidance by maintaining lower water deficit (WD) in the cells, dehydration tolerance at higher WD (Lascano et al 2001). Drought tolerance of crops is regarded as higher yield of a certain genotype compared to others at the same level of stress intensity (Fisher and Maurer 1978).…”
Section: Introductionmentioning
confidence: 99%
“…In previous works we have characterized wheat antioxidant system responses under drought, osmotic and photooxidative stresses (Lascano et al 2001(Lascano et al , 2003. With the aim of obtaining transgenic wheat plants, we adjusted a system by microprojectile bombardment, and obtained BASTA resistant plants .…”
Section: Introductionmentioning
confidence: 99%